Oral microflora in preschool children attending a fluoride varnish program: a cross-sectional study. Issue 1 (December 2016) - Anderson, Maria; Grindefjord, Margaret; Dahllöf, Göran; Dahlén, Gunnar; Twetman, Svante
Abstract Background To compare the oral microflora in preschool children attending a fluoride varnish program with a reference group receiving a standard oral health program without fluoride varnish applications. A second aim was to relate the microbial composition to the caries prevalence. Methods Five hundred seven 3-year-old children were enrolled from a cohort of 3403 preschool children taking part in a community based oral health project. Two hundred sixty-three of them had attended caries-preventive program with semi-annual applications of a fluoride varnish since the age of 1 year (test group) while 237 had received standard preventive care (reference group). Oral samples were collected with a sterile swab and analysed with checkerboard DNA-DNA hybridization using 12 pre-determined bacterial probes. Caries and background data were collected from clinical examinations and questionnaires. Results Gram-positive streptococci (S. intermedius, S. salivarius, S. oralis ) were most frequently detected and displayed the highest counts in both groups. There were no significant differences between the groups concerning prevalence of any of the selected bacterial strains except forS. oralis that occurred less frequently in the reference group. In children with caries, V. parvula were significantly more common (p < 0.05) while strains of Lactobacillus, Bifidobacterium and Neisseria were more prevalent among the caries-free children (p < 0.05). Conclusions A 2-year community program with semi-annual fluoride varnish applications did not seem to significantly influence the oral microflora in preschool children. Trial registration www.controlled-trials.com (ISRCTN35086887) 20131216 'retrospectively registered'.